Hungary : 2008 Article IV Consultation; Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The Article IV Consultation highlights the financial system risks that have increased reflecting both the global financial market turbulence and continued rapid credit growth in Hungary. With most new borrowing in foreign currency, the private sector's net foreign currency liabilities increased. Monetary policy has been appropriately tightened, and the elimination of the exchange rate band has removed a potential conflict between monetary policy objectives. Executive Directors called for enhanced collaboration with foreign supervisory authorities given Hungarian banks' close links with financial institutions abroad.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet